Can someone please help me –4x ≤ 36

Answers

Answer 1
Answer:

Answer:

x > -9

Step-by-step explanation:

–4x ≤ 36

Divide by -4, remembering to flip the inequality

-4x/-4 > 36/-4

x > -9


Related Questions

HELP ASAPPPPP!!!!!!!
A company produces two products, A and B. The sales volume for A is at least 80% of the total sales of both A and B. However, the company cannot sell more than 110 units of A per day. Both products use one raw material, of which the maximum daily availability is 300 lb. The usage rates of the raw material are 2 lb per unit of A, and 4 lb per unit of B The profit units for A and B are $40 and $90, respectively. Determine the optimal product mix for the company
HELP ME ANSWER THIS MGA LODI NG BAYAN HAHAHA SERIOUS NA ​
A human brain weighs about 1 kg and contains about 1011 cells. Assuming that each cell is completely filled with water (density = 1 g/mL), calculate the length of one side of such a cell if it were a cube. If the cells were spread out into a thin layer that was a single cell thick, what would be the total surface area (in square meters) for one side of the cell layer?
2y+5x=4 please help quickly

Factor completely: 4d^3+3d^2-14d

Answers

I got d(4d2+3d−14) hope it help

Solve the equation
log4x=2

Answers

Change it to exponential form:

log₄(x) = 2   ⇒   4² = x = 16

Final answer: 16

A box is in the shape of a triangular prism. . The base of the triangular face of the box is 11 centimeters (cm). The height of the triangular face of the box is 7.5 cm. The length of the box is 15 cm. V =1/2hxbxl What is the volume of the box? A 277.5 cm B 577.5 cm C 618.75 cm D1237.5 cm

Answers

Answer:

618.75  cm^(3)

Step-by-step explanation:

((11 cm)(7.5 cm)(15 cm))/(2) =618.75 cm^(3)

How do you do this question?

Answers

For A to B, or segment AB, we have the points (1,1) and (4,3). (x1, y1) = (1,1) and (x2, y2) = (4,3);

x = 1 + t(4 - 1)

y = 1 + t(3 - 1)

A to B => (x = 1 + 3t, y = 1 + 2t)

We can apply a similar process for BC and AC. For BC we have (x1, y1) = (4,3) and (x2,y2) = (1,7);

x = 4 + t(1 - 4)

y = 3 + t(7 - 3)

B to C => (x = 4 - 3t, y = 3 + 4t)

(x1, y1) = (1, 1) and (x2, y2) = (1, 7);

x = 1 + t(1 - 1)

y = 1 + t(7 - 1)

A to C => (x = 1, y = 1 + 6t)

Here is your graph of the triangle. Desmos is a really great tool to use;

1. An equation is shown below.3 (x-2) + 7x= 1/2(6x-2)
How many solutions, if any, does the equation have?

Answers

Answer:

x=5/7

Step-by-step explanation:

3(x-2)+7×=1/2×(6×-2)

3x-6+7×=1/2×2(3×-1)

3×-6+7×=3×-1

-6+7×=-1

7×=-1+6

7×=5

Please help! (95 points)

Answers

Answer:

303.61

Step-by-step explanation:

if you need explantion tell me and i will edit my answer

Answer:

24.4M

Step-by-step explanation: